Equation 3(x+3) -x= 2x+3
Essentially the goal is too make the two sides of the equation are equivalent , in my example above when simplified you come out with...
2x+3 = 2x+3
the same thing on both sides, therefor you could plug any value in for x or your variable and it would work
Another Example.
(y-7)(3)+x = 3y + x -21
When simplified
3y+x-21 = 3y+x -21
They are the same thing, therefor you can plug any value in for y , and this is why you can have an infinite number of solutions
I hope everything makes sense!